Perancangan Tata Kelola System Information Technology Incident Management Pada Laboratorium Komputer Stikom Surabaya - Mohamad Fanrauk Evero; Tutut Wurijanto; Erwin Sutomo (Jurnal Sistem Informasi Universitas Dinamika, 2016)
Abstract: STIKOM surabaya are the institutions that moves that puts forward in the fields of information and technology education. This is proven by the facilities and infrastructure that education be able to support the entire process. One of them is computer laboratories (labkom) that are located on the floor blue of stikom six buildings of surabaya. Labkom ever happened incident power lines fell, the incident had an impact on server down, and all the activity of going on labkom come to rest and wait for the recovery of server. The handling of the incident is now only management knowledge based server. Server added management if there is an incident recording and the provisin of this was not conducted the status of resolution, so if the incident happen then have to wait staff who know the improvement of the incident. The incident happened chronicled in detail should be complete by the time the events of server management. Based on the problems that occur on labkom currently, then in this research done making service sti procedure, namely standart operation procedure, work instructions, and work of a record using incident management in service operation - information technology infrastructure library ( ITIL ) v3 Google Search Google Translate Wikipedia Search YouTube Search Amazon Share Share:Google+ Facebook Twitter LinkedIn Reddit Email Google Search Google Translate Wikipedia Search YouTube Search Amazon Share Share:Google+ Facebook Twitter LinkedIn Reddit Email Google SearchGoogle TranslateWikipediaSearch YouTubeSearch AmazonShare Share:Google+ Facebook Twitter LinkedIn Reddit Email